A grey scale test pattern generator for testing APT recorders - SUBRAMANIAN, DV; PILLAI, KPB; IYER, LGS (MAUSAM, 1986)
A simple test pattern signal generator for testing ALDN APT recorders, is described and the results obtained are shown.